Monotherapy Anticoagulation to Expedite Home Treatment of Patients Diagnosed With Venous Thromboembolism in the Emergency Department: A Pragmatic Effectiveness Trial. Issue 7 (July 2021) - Kline, Jeffrey A.; Adler, David H.; Alanis, Naomi; Bledsoe, Joseph R.; Courtney, Daniel M.; d'Etienne, James P.; Diercks, Deborah B.; Garrett, John S.; Jones, Alan E.; Mackenzie, David C.; Madsen, Troy; Matuskowitz, Andrew J.; et al.
Abstract : Background: The objective was to test if low-risk emergency department patients with vitamin K antagonist (venous thromboembolism [VTE]; including venous thrombosis and pulmonary embolism [PE]) can be safely and effectively treated at home with direct acting oral (monotherapy) anticoagulation in a large-scale, real-world pragmatic effectiveness trial. Methods: This was a single-arm trial, conducted from 2016 to 2019 in accordance with the Standards for Reporting Implementation Studies guideline in 33 emergency departments in the United States. Participants had newly diagnosed VTE with low risk of death based upon either the modified Hestia criteria, or physician judgment plus the simplified PE severity index score of zero, together with nonhigh bleeding risk were eligible. Patients had to be discharged within 24 hours of triage and treated with either apixaban or rivaroxaban. Effectiveness was defined by the primary efficacy and safety outcomes, image-proven recurrent VTE and bleeding requiring hospitalization >24 hours, respectively, with an upper limit of the 95% CI for the 30-day frequency of VTE recurrence below 2.0% for both outcomes. Results: We enrolled 1421 patients with complete outcomes data, including 903 with venous thrombosis and 518 with PE. The recurrent VTE requiring hospitalization occurred in 14/1421 (1.0% [95% CI, 0.5%–1.7%]), and bleeding requiring hospitalization occurred in 12/1421 (0.8% [0.4%–1.5%). The rate of severe bleeding using International Society for Thrombosis and Haemostasis criteria was 2/1421 (0.1% [0%–0.5%]). No patient died, and serious adverse events occurred in 2.5% of venous thrombosis patients and 2.3% of patients with PE. Medication nonadherence was reported by patients in 8.0% (6.6%–9.5%) and was associated with a risk ratio of 6.0 (2.3–15.2) for VTE recurrence. Among all patients diagnosed with VTE in the emergency department during the period of study, 18% of venous thrombosis patients and 10% of patients with PE were enrolled. Conclusions: Monotherapy treatment of low-risk patients with venous thrombosis or PE in the emergency department setting produced a low rate of bleeding and VTE recurrence, but may be underused. Patients with venous thrombosis and PE should undergo risk-stratification before home treatment. Improved patient adherence may reduce rate of recurrent VTE. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03404635